We prove the derivative formula for \(\sin\text{;}\) the argument for \(\cos\) is very similar. Using the limit definition of the derivative, we have
\begin{align*}
\frac{d}{dx}(\sin x) \amp = \lim\limits_{h\to 0}\frac{\sin(x+h)-\sin x}{h}\\
\amp \lim\limits_{h\to 0}\frac{\sin x\cos h+\cos x\sin h-\sin x}{h}\\
\amp = \lim\limits_{h\to 0}\frac{\sin x(\cos h-1)}{h}+\frac{\cos x\sin h}{h}\\
\amp = \sin x\lim\limits_{h\to 0}\frac{\cos h-1}{h}+\cos x \lim\limits_{h\to 0}\frac{\sin h}{h} \\
\amp = \sin x\cdot 0 +\cos x\cdot 1\\
\amp = \cos x\text{,}
\end{align*}
where the penultimate step makes use of our previously discussed limits
\begin{align*}
\lim\limits_{t\to 0}\frac{\sin t}{t} \amp =1 \amp \lim\limits_{t\to 0}\frac{\cos t-1}{t}=0 \text{.}
\end{align*}